PENGGUNAAN POLA DAN BENTUK KOMUNIKASI DALAM PENERAPAN FUNGSI DAN PERAN KELUARGA - Sari, Afrina (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
This study aims to explain the use of patterns and forms of communication will be undertaken in the application of the function and role of the family. The research method uses descriptive correlational survey. Analyzed using the chi square (X ²) with inferential statistics, frequencies and percentages. Results showed that families of migrants who come from ethnic Malay, Batak, Nias, Minang, Palembang, Madurese, Bugis, Papua states that laissez-faire communication patterns include frequent and very often done by both types of families both families. Protective communication patterns are also included in the category often and very often done in communicating to both families both newcomers and families families resident natives. Pluralistic communication communication patterns fall into this category and included've often done in the family. Communication pattern is consensual communication patterns that include frequent and very often used in both types of families. Use of Communication patterns of laissez-faire, protective, pluralistic and consensual on the application of religious function, social function of culture, charity functions, protection functions, the function of reproduction, socialization function of education, economic functions, and environmental functions of all the family considers important and even essential